Multiphase computational fluid dynamics–conjugate heat transfer for spray cooling in the non-boiling regime. (March 2018) - Langari, M; Yang, Z; Dunne, JF; Jafari, S; Pirault, J-P; Long, CA; Jose, JT
A numerical study is described to predict, in the non-boiling regime, the heat transfer from a circular flat surface cooled by a full-cone spray of water at atmospheric pressure. Simulations based on coupled computational fluid dynamics and conjugate heat transfer are used to predict the detailed features of the fluid flow and heat transfer for three different spray conditions involving three mass fluxes between 3.5 and 9.43 kg/m 2 s corresponding to spray Reynolds numbers between 82 and 220, based on a 20 mm diameter target surface. A two-phase Lagrange–Eulerian modelling approach is adopted to resolve the spray-film flow dynamics. Simultaneous evaporation and condensation within the fluid film is modelled by solving the mass conservation equation at the film–continuum interface. Predicted heat transfer coefficients on the cooled surface are compared with published experimental data showing good agreement. The spray mass flux is confirmed to be the dominant factor for heat transfer in spray cooling, where single-phase convection within the thin fluid film on the flat surface is identified as the primary heat transfer mechanism. This enhancement of heat transfer, via single-phase convection, is identified to be the result of the discrete random nature of the droplets disrupting the surface of thin film.